Permodelan fizikal bagi kajian muara Sungai Langat - Suraya Sharil,; Othman A. Karim,; Sharifah Mastura Syed Abdullah, (2006)
This study examines the sediment plume behaviour as it enters the sea. It uses the physical model and remote sensing techniques. This paper will only discuss the application of physical model in suspended sediment study at Sg. Langat estuary. Sg Langat estuary model was built according to Froude criterion. It was designed as a fixed bed using distorted scale model. Sg. Langat estuary model was characterized into wavelength (L), wave height (H), wave period (T), current velocity (V) and wave celerity (c). Prototype analysis was made using calculated data from physical model using upscale equation. It shows that, there exists a scale effect on wave height (H) data. Sediment plume dispersion simulation in physical model proved the importance of wave in sediment movement